What Cut-off Value of 17-Hydroxyprogesterone Should Be an Indication to Perform a 250 µg Cosyntropin Stimulation Test When NCCAH Is Suspected? - a Retrospective Study - Domagala, Bartosz (J Endocr Soc, 2021)
The Nonclassic Congenital Adrenal Hyperplasia (NCCAH) is a less severe form of CAH in which the activity of the 21-hydroxylase is estimated at about 20% to 50%. Cosyntropin stimulation test is the gold diagnostic standard used to test for this condition. The study was aimed at verifying the currently accepted threshold of 17-hydroxyprogesterone (17OHP) level (≥2.0 ng/mL) at which cosyntropin stimulation test should be performed. Material and methods. The study included 343 patients (328 females and 15 males) referred for a cosyntropin stimulation test due to suspected NCCAH. The median age at the time of evaluation was 27 years. Serum 17-OHP was measured with ELISA assay using Ledect96 Microplate Reader. The NCCAH diagnosis was made if cosyntropin-stimulated 17OHP level exceeded 10.0 ng/mL. The ROC curve was determined, and the cut-off point with the highest sensitivity and specificity was established. The study was approved by the Ethics Board of JUMC. Results:. Symptoms, which prompted testing for NCCAH, most often were: hirsutism in 187 patients, irregular menstrual cycles in 178 patients, and acne in 138 patients. A total of 79 patients (77 females and two males) were diagnosed with NCCAH based on cosyntropin stimulation test results. Seventy-one of them had baseline levels of 17OHP≥2.0 ng/mL. The mean age of patients with confirmed NCCAH was 28.86 years. The baseline 17OHP cut-off value that qualified patients best for testing was 2.79 ng/mL in our group, with sensitivity and specificity of 77.2% and 91.3%, respectively. The sensitivity and specificity for a guideline-recommended cut-off point (17OHP ≥2.0 ng/mL) was 86.1% and 76%, respectively. In five of six patients with secondary amenorrhea and a baseline level of 17OHP ≥2.0 ng/mL, NCCAH was confirmed in a cosyntropin stimulation test. Conclusions:. Our results suggest considering an upward shift in the 17OHP threshold at which patients suspected for NCCAH should be referred for further evaluation. This may reduce the number of unnecessary cosyntropin stimulation tests, mainly that patients with mild phenotype (or asymptomatic) frequently may not require any treatment. However, attention should be paid to patients with coexisting secondary amenorrhea and 17OHP levels ≥2.0 ng/mL, which may be a clinical predictor of NCCAH.